Tensiomyographic contraction time of selected skeletal muscles in elite football players - Simunic, B. (2nd International scientific conference: Exercise and quality of life, Novi Sad. March 24/26th 2011, 2011)
Epidemiology research in football injuries is extensive; however there is lack of research in preventing injuries. Therefore, the motivation of our study was to introduce selected findings measured with tensiomyographic method, a potential muscle screening method in football related studies. The aim of our study was to evaluate selected skeletal muscles` Tensiomyographic contraction time (Tc) in players of elite football teams. We analysed Tc: (i) through development of young players in national teams from 13-year olds to seniors; (ii) in teams of various eliteness; and (iii) during whole season macro cycle. We found different developmental trends in different muscles; we found shorter Tc in more elite teams; and we showed longitudinal adaptation of muscles Tc during whole season macro cycle in selected team. Results of this study confirm longitudinal adaptation of selected muscles in football players.